A high-power graphite composite material, a preparation method and application thereof

CN117154044BActive Publication Date: 2026-10-30SHENZHEN GOLD MEDAL NEW ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311138660.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2026-10-30
Estimated Expiration
2043-09-01

AI Technical Summary

Technical Problem

由于加入金属元素提高材料石墨化度,即提高材料容量,但是由于石墨化后过渡金属微粉气化,留下的纳米孔洞,降低其材料的电子导电率,降低功率性能

Benefits of technology

[0024]本发明的第二个方面提供了一种高功率石墨复合材料,由上述制备方法得到。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117154044B_ABST
    Figure CN117154044B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of secondary battery materials, in particular to a high-power graphite composite material and a preparation method and application thereof, the preparation method comprises the following steps: S1. blending and reacting pretreated metal powder, a silane coupling agent, active particles and an organic solution to obtain modified metal powder; S2. blending and reacting the modified metal powder, a saccharide compound, graphite and a magnetic oxide to obtain hard carbon and metal-coated graphite material; and S3. blending and reacting the hard carbon and the metal-coated graphite material, pitch, an organic lithium salt and an organic solvent to obtain the graphite composite material. The electronic conductivity and strength of the material are improved by doping metal powder in the graphite shell, the orientation of the carbon material is changed by the magnetic oxide, the ion embedding channel of the material is improved, and the power performance is improved; meanwhile, the irreversible capacity of the material is reduced by the lithium compound coated on the outer layer, and the first efficiency, the cycle performance and the high-temperature storage performance of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of secondary battery materials technology, and in particular to a high-power graphite composite material, its preparation method, and its application. Background Technology

[0002] Currently, commercially available lithium-ion battery anode materials are mainly made of artificial graphite. Because the interlayer spacing of graphite is smaller than the interlayer spacing of graphite lithium intercalation compounds, the graphite interlayer spacing changes during charging and discharging, easily causing graphite layer peeling and pulverization. Furthermore, graphite has a layered structure, resulting in a longer lithium-ion insertion / extraction path and lower isotropy during charging and discharging, leading to deviations in rate performance. Although the electronic conductivity of the material can be improved by coating or doping with graphene or amorphous carbon, which have high electronic conductivity, the ionic conductivity is not improved, and the rate performance improvement is not significant. Metals, as materials with high electronic conductivity, can be doped into graphite to improve its electronic conductivity; however, metals have poor high-temperature storage performance, so lithium salts are often coated on their surface to improve high-temperature storage performance. For example, patent application CN201510338421.X discloses a method for producing high-capacity artificial graphite anode material for lithium-ion batteries. The method uses petroleum coke powder as raw material A, pitch powder as raw material B, and single-transition metal powder or a mixture of multiple transition metal powders as raw material C. Raw materials A and C are then subjected to graphitization and other processes to obtain the anode material. While adding metal elements increases the degree of graphitization, thus increasing the material's capacity, the vaporization of the transition metal powders after graphitization leaves behind nanopores, reducing the material's electronic conductivity and power performance.

[0003] Therefore, the anode materials prepared in the existing technology are still difficult to achieve the power performance, first-pass efficiency and rate performance of graphite. Summary of the Invention

[0004] To improve the power performance of graphite, this invention enhances the electronic conductivity of the material by doping the outer shell with metals and their magnetic oxides and changing the orientation of the carbon-based material. This improves the electronic conductivity and isotropy of the coating layer, thereby enhancing the power performance. Simultaneously, the outer shell is doped with lithium salts with high ionic conductivity to improve the material's initial efficiency and rate performance.

[0005] The first aspect of the present invention provides a method for preparing a high-power graphite composite material, the method comprising the following steps:

[0006] S1. The pretreated metal powder is mixed with silane coupling agent, active particles and organic solution to obtain modified metal powder;

[0007] S2. Modified metal powder is blended with carbohydrates, graphite, and magnetic oxides to obtain hard carbon and metal-coated graphite materials;

[0008] S3. Hard carbon and metal-coated graphite materials are blended and reacted with asphalt, organolithium salts, and organic solvents to obtain the graphite composite material.

[0009] In some embodiments, the metal powder includes at least one of silver powder, copper powder, nickel powder, cobalt powder, and iron powder.

[0010] Furthermore, the particle size of the metal powder is 80-120 nm.

[0011] Furthermore, the pretreatment of the metal powder includes ultrasonically washing the metal powder with ethanol followed by drying.

[0012] In some embodiments, the mass ratio of the metal powder to the silane coupling agent, active particles, and organic solution is 100:(1-10):(0.5-2):(500-1000).

[0013] Furthermore, the silane coupling agent may be selected from some commonly used types in the art, including but not limited to γ-aminopropylmethyldiethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0014] In some embodiments, the active particles include at least one of silver chloride, cobalt chloride, palladium chloride, and nickel chloride.

[0015] Furthermore, the organic solution may be selected from those commonly found in the art, including but not limited to at least one of n-hexane, xylene, carbon disulfide, and carbon tetrachloride.

[0016] In this invention, the modification of metal powder by using silane coupling agents and active particles can enhance the activity of the material, which is beneficial for the insertion and extraction of lithium ions during the charging and discharging of the composite material. At the same time, the silane coupling agent coating on the surface of the material can improve the structural stability of the material. The silicon oxide compound formed after carbonization can improve the specific capacity of the material. In particular, when the mass ratio of metal powder to silane coupling agent, active particles and organic solution is 100:(1-10):(0.5-2):(500-1000), it has better kinetic performance and tap density effect. If the content of silane coupling agent and active particles is too high, it will reduce the cycle performance and storage performance of the material. If it is too low, the improvement in the kinetic performance of the material will not be significant.

[0017] In some embodiments, the mass ratio of the modified metal powder to the carbohydrate compound, graphite, and magnetic oxide is (1-5):(10-20):100:(0.5-2).

[0018] Furthermore, the carbohydrate compound includes at least one of glucose, sucrose, lignin, starch, and cellulose.

[0019] In some embodiments, the magnetic oxide includes at least one of iron tetroxide, cobalt tetroxide, and nickel tetroxide.

[0020] When the mass ratio of modified metal powder to carbohydrate compound, graphite, and magnetic oxide is (1-5):(10-20):100:(0.5-2), the material exhibits good rate performance, electrode adhesion, and specific capacity. If the mass ratio is too high, there will be more magnetic oxides, resulting in higher activity, which will reduce high-temperature storage performance and increase self-discharge. If the mass ratio is too low, there will be fewer magnetic oxides, resulting in a more regular arrangement of carbon-based materials, a larger OI value, and poorer kinetics.

[0021] In some embodiments, the mass ratio of the hard carbon and metal-coated graphite material to asphalt, organolithium salt, and organic solvent is 100:(1-30):(1-5):(500-1000).

[0022] In some embodiments, the organolithium salt includes at least one of lithium tetrafluoroborate, lithium bis(oxalate)borate, lithium difluorooxalateborate, lithium difluorobis(oxalate)phosphate, and lithium tetrafluorooxalate phosphate.

[0023] The composite material of this invention has an organic lithium salt coated on the metal surface, which has high compatibility with electrolyte and strong adhesion of the coating layer, reduces the electron density of the material, and the organic lithium salt has a faster lithium ion diffusion rate under low temperature conditions, thus improving the low temperature performance of the material.

[0024] A second aspect of the present invention provides a high-power graphite composite material obtained by the above preparation method.

[0025] A third aspect of the invention provides the application of high-power graphite composite materials in the preparation of secondary battery anode materials.

[0026] Compared with the prior art, the present invention has the following beneficial effects: by doping metal powder into the graphite shell, the electronic conductivity and strength of the material are improved, and the magnetic oxide changes the orientation of the carbon material to improve the ion insertion channel of the material and improve the power performance; at the same time, the lithium compound coated on the outer layer reduces the irreversible capacity of the material and improves the first efficiency, cycle performance and high temperature storage performance of the material. Attached Figure Description

[0027] Figure 1 The image shows a SEM image of the high-power graphite composite material prepared in Example 1. Detailed Implementation

[0028] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] Example 1

[0030] This embodiment provides a high-power graphite composite material, the preparation method of which includes the following steps:

[0031] S1. 100g of silver powder (particle size 100nm) was washed with ethanol, ultrasonically cleaned and dried. It was then dispersed evenly with 5g of γ-aminopropylmethyldiethoxysilane, 1g of silver chloride and 800g of toluene organic solution. The mixture was then transferred to a high-pressure reactor and reacted at 100℃ for 120min to obtain modified metal powder.

[0032] S2. Add 3g of modified metal powder to 150g of 10wt% glucose aqueous solution, and add 100g of artificial graphite and 1g of iron oxide and disperse evenly. Then transfer to a high-pressure reactor and react at 200℃ for 3h. Filter, vacuum dry at 80℃ for 24h, and then heat to 1300℃ for 3h to carbonize to obtain hard carbon and metal-coated graphite material.

[0033] S3. Add 20g of petroleum asphalt to 800g of n-hexane organic solvent and disperse evenly. Then add 3g of lithium tetrafluoroborate and disperse evenly. Then add 100g of hard carbon and metal-coated graphite material and ultrasonically disperse evenly. React at 150℃ for 3h, filter, vacuum dry at 80℃ for 24h, then transfer to a tube furnace and carbonize at 900℃ for 3h under an argon inert atmosphere at a heating rate of 5℃ / min to obtain the graphite composite material.

[0034] Example 2

[0035] This embodiment provides a high-power graphite composite material, the preparation method of which includes the following steps:

[0036] S1. 100g of copper powder (particle size 100nm) was washed with ethanol, ultrasonically cleaned and dried. It was then dispersed evenly with 1g of γ-aminopropyltrimethoxysilane, 0.5g of nickel chloride and 500g of xylene organic solution. The mixture was then transferred to a high-pressure reactor and reacted at 50℃ for 300min to obtain modified metal powder.

[0037] S2. Add 1g of modified metal powder to 100g of 10wt% sucrose aqueous solution, and add 100g of artificial graphite and 0.5g of nickel tetroxide and disperse evenly. Then transfer to a high-pressure reactor and react at 150℃ for 6h. Filter, vacuum dry at 80℃ for 24h, and then heat to 1200℃ for 6h to obtain hard carbon and metal-coated graphite material.

[0038] S3. Add 10g of coal tar pitch to 500g of xylene organic solvent and disperse evenly. Then add 1g of lithium bis(oxalate-borate) and disperse evenly. Then add 100g of hard carbon and metal-coated graphite material and ultrasonically disperse evenly. React at 100℃ for 6h, filter, vacuum dry at 80℃ for 24h, then transfer to a tube furnace and carbonize at 700℃ for 6h under an argon inert atmosphere at a heating rate of 1℃ / min to obtain the graphite composite material.

[0039] Example 3

[0040] This embodiment provides a high-power graphite composite material, the preparation method of which includes the following steps:

[0041] S1. 100g of cobalt powder (particle size 100nm) was washed with ethanol, ultrasonically cleaned and dried, and then reacted with 10g of γ-aminopropyltriethoxysilane, 2g of cobalt chloride and 1000g of carbon tetrachloride organic solution at 150℃ for 30min to obtain modified metal powder.

[0042] S2. Add 5g of modified metal powder to 200g of 10wt% starch aqueous solution, and add 100g of artificial graphite and 2g of cobalt tetroxide and disperse evenly. Then transfer to a high-pressure reactor and react at 250℃ for 1h. Filter, vacuum dry at 80℃ for 24h, and then heat to 1500℃ for 1h to carbonize to obtain hard carbon and metal-coated graphite material.

[0043] S3. Add 30g of petroleum asphalt to 1000g of carbon tetrachloride organic solvent and disperse evenly. Then add 5g of lithium difluorooxalate borate and disperse evenly. Then add 100g of hard carbon and metal-coated graphite material and ultrasonically disperse evenly. React at 200℃ for 1h, filter, vacuum dry at 80℃ for 24h, then transfer to a tube furnace and carbonize at 1200℃ for 1h under an argon inert atmosphere at a heating rate of 10℃ / min to obtain the graphite composite material.

[0044] Comparative Example 1

[0045] This comparative example provides a high-power graphite composite material, with the specific implementation method being the same as in Example 1, except that...

[0046] S1. Add 3g of copper powder (particle size 100nm) to 150g of 10wt% glucose aqueous solution, and add 100g of artificial graphite and 1g of iron oxide and disperse evenly. Then transfer to a high-pressure reactor and react at 200℃ for 3h. Filter, vacuum dry at 80℃ for 24h, and then heat to 1300℃ for 3h to carbonize to obtain hard carbon and metal-coated graphite material.

[0047] S2. Add 20g of petroleum asphalt to 800g of n-hexane organic solvent and disperse evenly. Then add 3g of lithium tetrafluoroborate and disperse evenly. Then add 100g of hard carbon and metal-coated graphite material and ultrasonically disperse evenly. React at 150℃ for 3h, filter, vacuum dry at 80℃ for 24h, then transfer to a tube furnace and carbonize at 900℃ for 3h under an argon inert atmosphere at a heating rate of 5℃ / min to obtain the graphite composite material.

[0048] Comparative Example 2

[0049] This comparative example provides a high-power graphite composite material, with the same specific implementation method as Example 1, except that the lithium tetrafluoroborate is 0g.

[0050] Comparative Example 3

[0051] This comparative example provides a high-power graphite composite material, with the same specific implementation method as Example 1, except that the amount of silver chloride is 13g.

[0052] Comparative Example 4

[0053] This comparative example provides a high-power graphite composite material, with the specific implementation method being the same as in Example 1, except that the amount of iron(III) oxide is 5g.

[0054] Performance testing

[0055] 1. The high-power graphite composite material prepared in Example 1 was subjected to SEM testing, and the results are as follows: Figure 1 As shown in the figure, the graphite composite material prepared in Example 1 exhibits a spherical structure with uniform size distribution and a particle size between 10-15 μm.

[0056] 2. Physical and chemical properties and button cell testing

[0057] The graphite composite materials prepared in Examples 1-3 and Comparative Examples 1-4 were tested for particle size, tap density, specific surface area, powder OI value, and specific capacity. Test method: GBT-24533-2019 "Graphite Anode Materials for Lithium-ion Batteries". The powder OI value was tested by XRD, and the OI value of the material was calculated.

[0058] The graphite composite materials obtained in Examples 1-3 and Comparative Examples 1-4 were assembled into button cells. The preparation method was as follows: binder, conductive agent and solvent were added to the negative electrode material, stirred and slurryed, coated on copper foil, and dried and rolled. The binder used was LA132 binder, the conductive agent was SP, and the negative electrode material was the hard carbon material prepared in Examples 1-3 and Comparative Examples 1-4, respectively. The solvent was double-distilled water, and the ratio was: negative electrode material: SP: LA132: double-distilled water = 94g: 2g: 4g: 220mL, and a negative electrode sheet was prepared. The electrolyte was LiPF6 / EC+DEC (volume ratio 1:1, concentration 1.1mol / L), the counter electrode was lithium metal sheet, and the separator was polyethylene (PE), polypropylene (PP), or polyethylene propylene (PEP) composite membrane. The simulated battery was assembled in an argon-filled glove box, and the electrochemical performance was tested on a Wuhan Landian CT2001A battery tester. The charge and discharge voltage range was 0.005V to 2.0V, and the charge and discharge rate was 0.1C. Simultaneously, the rate capability (1C / 0.1C), cycle performance (0.2C / 0.2C, 100 cycles), and charge DCR (50% SOC) of its coin cells were tested. The diffusion coefficient of its example and comparative materials was also tested using GITT. The test results are shown in Table 1 below:

[0059] Table 1

[0060]

[0061]

[0062] As can be seen from Table 1, compared with Comparative Example 1, the graphite composite materials prepared in Examples 1-3 showed significantly improved initial discharge capacity, initial efficiency, rate performance, and cycle performance. This is because the doping of metal sheets into the graphite shell increases the electronic conductivity of the material, improves the rate performance, and enhances the specific capacity of the material. At the same time, the lithium compound coating on the outer layer reduces the irreversible capacity of the material and improves the initial efficiency.

[0063] 3. Soft-pack battery test:

[0064] The graphite composite materials prepared in Examples 1-3 and Comparative Examples 1-4 were used as negative electrodes, respectively, and ternary materials (LiNi) were used. 1 / 3 Co 1 / 3 Mn 1 / 3 A positive electrode was prepared using O2 as the positive electrode material, and a 2Ah soft-pack battery was prepared using LiPF6 (solvent EC+DEC, volume ratio 1:1, concentration 1.3mol / L) as the electrolyte and Celegard 2400 as the separator.

[0065] 3.1x Ratio Performance Test

[0066] The charge / discharge voltage range was 2.8–4.2V, and the test temperature was 25±3.0℃. The battery was charged at 1.0C, 2.0C, 3.0C, and 5.0C, and discharged at 1.0C. The constant current ratio of the battery was tested under different charging modes, and the results are shown in Table 2.

[0067] Table 2

[0068] Example 1 Constant current ratio (%) 95.78 92.79 87.39 79.45 Example 2 Constant current ratio (%) 94.13 91.35 86.82 78.28 Example 3 Constant current ratio (%) 96.92 93.94 88.56 80.23 Comparative Example 1 Constant current ratio (%) 91.68 88.37 83.23 68.98 Comparative Example 2 Constant current ratio (%) 90.33 87.58 82.22 66.56 Comparative Example 3 Constant current ratio (%) 92.13 89.89 85.21 70.34 Comparative Example 4 Constant current ratio (%) 92.10 88.98 85.13 69.87

[0069] As shown in Table 2, the rate charging performance of the battery pack of the present invention is significantly better than that of the comparative example, and the charging time is shorter, indicating that the composite negative electrode material of the present invention has good fast charging performance. This may be because the material in the examples has a lower OI value, which improves the material's kinetic properties, and simultaneously, the material in the examples has a high specific surface area, which improves the material's rate performance.

[0070] 3.2 Cyclic Performance Test

[0071] The soft-pack batteries made using the graphite composite materials in Examples 1-3 and the comparative examples were subjected to the following experiments: 500 charge-discharge cycles were performed at a 1C / 1C charge-discharge rate and a voltage range of 2.8-4.2V to test their capacity retention rate and the charge DCR after 500 cycles. The results are shown in Table 3.

[0072] Table 3

[0073]

[0074] As can be seen from Table 3, the lithium-ion battery prepared by the graphite composite anode material obtained in this invention has better cycle performance than the comparative example. This may be because the lithium compound coating on the graphite surface increases the number of lithium ions transported during charging and discharging, thus improving cycle performance. At the same time, the excellent diffusion coefficient of the examples reduces DCR.

[0075] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a high-power graphite composite material, characterized in that, The preparation method includes the following steps: S1. The pretreated metal powder is mixed with silane coupling agent, active particles and organic solution to obtain modified metal powder; The metal powder includes at least one of silver powder, copper powder, nickel powder, cobalt powder, and iron powder. The active particles include at least one of silver chloride, cobalt chloride, palladium chloride, and nickel chloride; The mass ratio of metal powder to silane coupling agent, active particles, and organic solution is 100:(1-10):(0.5-2):(500-1000); S2. The modified metal powder is mixed with carbohydrate compounds, graphite, and magnetic oxides and then heated for carbonization to obtain hard carbon and metal-coated graphite materials; The mass ratio of the modified metal powder to the carbohydrate compound, graphite, and magnetic oxide is (1-5):(10-20):100:(0.5-2). S3. Hard carbon and metal-coated graphite materials are mixed with asphalt, organic lithium salts, and organic solvents, and then heated to carbonize, thereby obtaining the graphite composite material.

2. The preparation method according to claim 1, characterized in that, The magnetic oxide includes at least one of iron tetroxide, cobalt tetroxide, and nickel tetroxide.

3. The preparation method according to claim 1, characterized in that, The mass ratio of the hard carbon and metal-coated graphite material to asphalt, organic lithium salt, and organic solvent is 100:(1-30):(1-5):(500-1000).

4. The preparation method according to claim 1, characterized in that, The organic lithium salt includes at least one of lithium tetrafluoroborate, lithium bis(oxalate)borate, lithium difluorooxalateborate, lithium difluorobis(oxalate)phosphate, and lithium tetrafluorooxalate phosphate.

5. A high-power graphite composite material, characterized in that, It is obtained by the preparation method according to any one of claims 1-4.

6. The application of the high-power graphite composite material according to claim 5 in the preparation of secondary battery anode materials.

Citation Information

Patent Citations

  • Production method of artificial graphite anode material for high-capacity lithium ion battery

    CN104900878A

  • High-power graphite composite material and preparation method thereof

    CN114122391A

  • Fast-charging graphite composite material and preparation method thereof

    CN115528231A